Patterns of Chinese adolescents' activity preferences: Predictors and associations with time spent on physical and sedentary activities. (May 2021) - Ma, Zhuanzhuan; He, Jinbo; Lu, Tom
Highlights: Three latent classes were identified for Chinese adolescents' activity preferences. Several predictors (e.g., residence) were related to different patterns of activity preferences. Participants in different classes differed in the time spent on physical and sedentary activities. Abstract: The purpose of this study was to explore the patterns of Chinese adolescents' activity preferences as well as the predictors and associations with the actual time spent on physical and sedentary activities. With the data set derived from the China Health and Nutrition Survey (CHNS), latent class analysis (LCA) was employed to analyze data of 501 adolescents in the age range of 12–17 years old. The results showed that three distinct groups of activity preferences were identified: like all (21.6%, n = 108), like media more than sports (52.9%, n = 265), and like none (25.5%, n = 128). Major predictors for activity preferences included residence, sleeping hours, dietary knowledge, and life attitudes. The results revealed that adolescents in different patterns had statistically significant differences in the weekly participating time on physical activities (e.g. martial arts, track and field/running/swimming, walking, soccer/basketball/tennis, badminton/volleyball, and other/ping pong/Tai Chi) as well as sedentary activities (e.g. watching TV, watching movies and videos online, surfing internet, chatting online, playing computer/smartphone games, doing homework, playing toy cars/puppets/board games, engaging in extracurricular reading/writing/drawing) among the three latent classes. Implications and future research directions are discussed.